2015
DOI: 10.1111/padm.12183
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Leadership and the Changing Governance of Public Hospitals: Implications for Patient Experience

Abstract: A growing evidence base suggests that increasing the involvement of clinical professionals on governing boards of hospitals has a positive impact on organizational performance.However, less is known about the wider conditions that influence this process and whether recent moves to restructure the governance of public hospitals, extending their formal autonomy, has made any difference to the outcome of clinical involvement on patient experience. Using four years of data and concentrating on the acute hospital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 42 publications
4
34
1
Order By: Relevance
“…Turning our attention to the European settings, Veronesi et al [ 12 ] report that a greater ratio of clinical members on governing boards of English hospital trusts generates better ratings of the quality of the service provided, as well as being associated with a reduction in morbidity rates. In a later study, Veronesi et al [ 39 ] also show that the involvement of clinicians on the board of directors improves the overall patient experience of the care provided by acute hospitals when clinical managers operate in a more autonomous organisational form. A similar methodology was also applied to the Italian NHS, where Sarto and colleagues [ 22 ] find a positive correlation between the clinical background of public hospital CEOs and quality outcomes, measured as medical and surgical appropriateness as well as patient length of stay in hospital.…”
Section: Analysis Of the Literaturementioning
confidence: 99%
“…Turning our attention to the European settings, Veronesi et al [ 12 ] report that a greater ratio of clinical members on governing boards of English hospital trusts generates better ratings of the quality of the service provided, as well as being associated with a reduction in morbidity rates. In a later study, Veronesi et al [ 39 ] also show that the involvement of clinicians on the board of directors improves the overall patient experience of the care provided by acute hospitals when clinical managers operate in a more autonomous organisational form. A similar methodology was also applied to the Italian NHS, where Sarto and colleagues [ 22 ] find a positive correlation between the clinical background of public hospital CEOs and quality outcomes, measured as medical and surgical appropriateness as well as patient length of stay in hospital.…”
Section: Analysis Of the Literaturementioning
confidence: 99%
“…The results show that organisations, and hospitals in particular, would be better off increasing the overall level of heterogeneity in their boardrooms as this leads to improved overall organisational performance. This finding is particularly significant given the increasing pressures on public sector organisations, and specifically hospitals, to not only improve the quality of services and the efficient use of resources, but also to improve the experience of patients (Veronesi, Kirkpatrick, & Altanlar, 2015). Furthermore, the study emphasises how line managers play a crucial role in relation to staff satisfaction in particular with reference to motivation levels of employees, their perception of the organisation as a positive place to work in and, in general, their contentment with the managerial styles and practices adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Simple, easy-to-action findings also exist. For example, Veronesi et al 4 found a quality premium associated with increased numbers of clinicians on trust boards. Interestingly, the improvement (in patient experience) was only significant when clinician numbers were four or more with five yet more significant.…”
mentioning
confidence: 99%